CONCEPTUALIZING THE EFFECTIVENESS RESEARCH OF AN ONLINE CURRICULUM FOR VIRTUE EDUCATION IN LATVIA - Fernández González, Manuel Joaquín; Surikova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The necessity and unavoidability of moral education in school is well established, but there is still a lack of theoretical knowledge base (know-what) regarding what works effectively in character education. This paper addresses the conceptualization of a 3-year effectiveness research of the online curriculum for virtue education from grades 1 to 9. The goal of the research is to create new theoretical knowledge about what means effective moral education and about what makes an online curriculum for virtue education effective in Latvian context. The effectiveness research uses the randomised controlled trial approach and adopts an experimental trial design, using pre-, intermediate- and post-test with experiment and control groups clustered at the class level in three strata: grades 2-4, grades 5-7, and grades 7-9. The intervention will consist of the implementation of the full virtue education curriculum in the respective grades. A multicomponent questionnaire for pupils and focus-group discussion with teachers are used for data collection. The curriculum is highly coherent with global, national and sector priorities and has a strong potential for enhancing the quality of education and contributing to societal well-being in Latvia.